2022
DOI: 10.1007/s13127-021-00535-7
|View full text |Cite
|
Sign up to set email alerts
|

Phyllidiidae (Nudibranchia, Heterobranchia, Gastropoda): an integrative taxonomic approach including chemical analyses

Abstract: Members of the widely distributed and common nudibranch family Phyllidiidae are often easily spotted in the marine environment because of their conspicuous colours and obvious presence on the reef. They are interesting with regard to their defensive chemical compounds that may lead to new drug discoveries. Despite their abundance, the family is also well known for its taxonomic problems and the difficulties in species identification due to very similarly coloured species and lack of morphological characters. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 107 publications
1
0
0
1
Order By: Relevance
“…Okino et al [81] suggested that sesquiterpenes present in the mucus may serve as antifouling agents to keep exposed surfaces free of epibionts, and that Phyllidia compounds also utilize a dense layer of calcareous spicules arranged on the mantle and foot, which provide structural support and make them difficult to eat, acting as a defense mechanism. The most detected secondary metabolites in the three analyzed Phyllidia genera are sponge-derived sesquiterpene isonitrile and related compounds, which agrees with chemical investigations prior to the Papu et al [82] and a common feature of all chemically analyzed Phyllidia species is the presence of brominated natural products that have moderate polarity.…”
Section: Biological /Pharmacological Activities Of Secondary Metaboli...supporting
confidence: 87%
“…Okino et al [81] suggested that sesquiterpenes present in the mucus may serve as antifouling agents to keep exposed surfaces free of epibionts, and that Phyllidia compounds also utilize a dense layer of calcareous spicules arranged on the mantle and foot, which provide structural support and make them difficult to eat, acting as a defense mechanism. The most detected secondary metabolites in the three analyzed Phyllidia genera are sponge-derived sesquiterpene isonitrile and related compounds, which agrees with chemical investigations prior to the Papu et al [82] and a common feature of all chemically analyzed Phyllidia species is the presence of brominated natural products that have moderate polarity.…”
Section: Biological /Pharmacological Activities Of Secondary Metaboli...supporting
confidence: 87%
“…Analisis kimia menunjukkan bahwa jenis ini menggunakan jenis sponge tertentu sebagai makanan; namun, banyak jenis menunjukkan susunan yang luas senyawa dan karena itu lebih dicirikan oleh komposisi atau profilnya daripada senyawa yang berbeda atau unik. (Papu, et al, 2021) Kelompok nudibranch yang ditemukan dalam jumlah yang relatif lebih sedikit dari kelompok pertama, terdiri dari jenis Baeolidia nodosa, Berghia coerulescens, Chelidonura pallida, Bornella sp, Halgerda carlsoni, Jorunna funebris, Asteronotus cespitosus, Thuridilla bayeri, Thuridill. T. gracilis, Caloria indica, Flabellina exoptata, Hexabranchus sanguineus, Ercolania sp, dan Pleurobranchus forskalii, seperti ditunjukkan dalam Tabel 2.…”
Section: Hasil Dan Pembahasanunclassified